Evaluation of Transport Roads at PT Aneka Tambang Tbk's Pakal Island Site, East Halmahera Regency, North Maluku Province - Muhammad Djunaidi; Sarna Winsi Harun; Husaen Salahu (UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2026)
PT. Aneka Tambang Tbk is one of the companies engaged in the laterite nickel mining industry operating in East Halmahera Regency, using the open cut mining method. Based on field observations, during the rainy season, the roads are often slippery and muddy, and the road surface becomes bumpy because hauling activities are carried out even during the rainy season. During the dry season, the roads become dusty, which can interfere with the visibility of transport unit drivers. The road width complies with the American Association of State Highway and Transportation Officials (AASHTO) standard of 12.25 meters. The width of the road is 14.2 meters in segments 1-2, 13 meters in segments 3-4, and 14.3 meters in segments 5-6, which can be safely traversed, while the width of the straight road in segment 7 does not meet AASHTO standards. - Segment 8 is 10 meters wide, so an additional 2.25 meters of road width must be added to ensure safe passage. The transport road width at turns that complies with AASHTO standardization is 26.82 meters. This is found in segments 1 - segment 2, which is 28.3 meters, segments 3 - segment 4, which is 27.6 meters, and segments 5 - segment 6, which is 28 meters, so it can be passed safely.